Social Impact Assessment in the Cooperative Extension System: Revitalizing the Community Capitals Framework in Measurement and Approach - Abigail Borron; Kevan Lamm; Carolina Darbisi; Nekeisha Randall (Journal of International Agricultural and Extension Education, 2019)
Measuring program impact is continually placed in the forefront of discussions, efforts, and reporting when it comes to outreach and engagement efforts related to Cooperative Extension. However, the diversity of programs represented through program areas, as well as the complexities of local infrastructures present ongoing challenges to effectively addressing needs in community development and vitality. One of the greater hurdles in these efforts is addressing areas of social impact. This article argues for a deliberate attempt to parse out efforts that address social impact, while looking for ways to bring such impact full circle with existing efforts in economic impact. This article answers the following questions: (1) How is program impact defined as it relates to the land-grant university? and (2) How is social impact defined, and what are the common approaches to examining/measuring social impact? Based on this review of the literature, we describe and justify a proposed model approach for overall community diagnostics, directly supporting social impact assessment efforts. Such a proposed model would then have the capacity to lead to two very distinct and applicable outcomes that ultimately lead to measuring and examining program impact. The first is an immediate snapshot of a given community for diagnostic purposes; and the second would create a framework by which longitudinal data could be collected, which can then demonstrate changes and shifts over time. Such data can then provide a more holistic approach to program planning, development, and overall evaluation.
Keywords: community development; Extension; needs assessment; program evaluation; social impact